Trained health extension workers correctly identify high blood pressure in rural districts of northwest Ethiopia: a diagnostic accuracy study - Destaw Fetene Teshome; Shitaye Alemu Balcha; Tadesse Awoke Ayele; Asmamaw Atnafu; Mekonnen Sisay; Marye Getnet Asfaw; Getnet Mitike; Kassahun Alemu Gelaye (BMC, 2022)
Abstract Background Hypertension is a public health issue in Ethiopia. The vast majority of cases remain undiagnosed and untreated. Early and accurate identification of hypertension can help with timely management and reduce the risk of complications. In resource-constrained rural settings where poor access to care and a shortage of healthcare providers are major barriers, task-sharing of some primary healthcare duties from well-trained healthcare workers to community health workers has been found to be a cost-effective strategy. This study aimed to assess the ability of trained health extension workers to correctly identify high blood pressure among adults in rural areas of northwest Ethiopia. Methods A cross-sectional study was conducted in rural areas of northwest Ethiopia from June to October 2020. Trained health extension workers and health professionals measured the blood pressure of 1177 study participants using a calibrated aneroid sphygmomanometer. A Kappa test statistic was used to compare the two sets of measurements for agreement. The sensitivity, specificity, positive, and negative predictive values were used to assess the validity of health extension workers' ability to identify high blood pressure in comparison to health professionals. Results The trained health extension workers and health professionals identified 219 (18.6%) and 229 (19.5%) of the participants with high blood pressure, respectively. The inter-rater agreement between health extension workers and health professionals for high blood pressure detection was 91.2% (k = 0.912, 95% CI: 0.88, 0.94, p-value = 0.000). The sensitivity and specificity of high blood pressure detection by health extension workers were 90.8% (95% CI: 89.6, 92.0) and 98.8% (95% CI: 98.1, 99.5), respectively. While the positive and negative predictive values were 95.0% (95% CI: 92.1, 97.9) and 97.8% (95% CI: 97.3, 98.3), respectively. Conclusions The inter-rater agreement between the trained health extension workers and health professionals on high blood pressure detection was excellent. The findings indicate that training health extension workers is a reliable and valid strategy for early detection of hypertension. Thus, the strategy can be integrated with the essential services provided by primary health care units at the village and health post level in rural settings.